Silencing the gustatory receptor BtGR11 affects the sensing of sucrose in the whitefly Bemisia tabaci - Li, Fengqi; Di, Zhongjuan; Tian, Jiahui; Dewer, Youssef; Qu, Cheng; Yang, Shiyong; Luo, Chen (Frontiers in Bioengineering and Biotechnology, 2022)
RNA interference (RNAi) is powerful biotechnology for studying the in vivo functions of key genes. Based on this property, RNAi can also be used for pest control as an effective alternative to chemical pesticides. The management of phloem-sucking pests is a tricky issue in current agricultural and forestry pest control. RNAi can silence key chemoreceptor genes of phloem-sucking pests; thereby regulating the behavior of these pests can be manipulated. So, it is considered to be a promising new type of ecological pest management strategy. In this study, we identified a candidate taste receptor gene,BtGR11, that controls the taste sensitivity to sucrose in the whitefly Bemisia tabaci, which is a serious invasive phloem-sucking pest worldwide. Functional analyses using the Xenopus oocyte expression system and the two-electrode voltage-clamp system revealed that the oocytes expressing BtGR11 responded to sucrose. Furthermore, we found that silencing BtGR11 by RNAi inhibited the function of sensing sucrose in the whitefly. This study reports a key chemoreceptor gene that can be used for the understanding of the gustatory sensing mechanisms of whitefly to deterrent.